Strategic Imagination - Fanel Stroe (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
The usefulness of strategic imagination is one of the coveted competitive advantages today. I present some of the moments of itshistorical evolution and some of the social architectures that can generate it.